Status of heavy metal pollution of water and fishes in Balu and Brahmaputra rivers - Rahman, MM; Islam, MA; Khan, MB (Progressive Agriculture, 2017)
The study was conducted to investigate the surface water quality and concentration of heavy metals in water and fish of the Balu and Brahmaputra rivers near to Demra in Dhaka city and BAU campus in Mymensingh respectively. Water samples were collected in distinct three sampling sites which were denoted as Station 1, Station 2 and Station 3. In Balu and Brahmaputra river, analysis of physicochemical parameters like temperature, transparency, pH, electrical conductivity (EC), total dissolved solid (TDS), dissolved oxygen (DO), biochemical oxygen demand (BOD) and alkalinity and the concentration of heavy metals (Pb, Cr, Cd, Cu, Ni, Zn) both water and three fish (Mastacembelus armatus, Channa punctatus and Mystus vittatus) species were analyzed. The comparative study reported that some physicochemical parameters like TDS (704±8.54 mg/l); EC (1043±39.15 mg/l), BOD (22±3 mg/l), and alkalinity (311±6.56 mg/l) of Balu river water were found much higher than Brahmaputra river where as transparency (10±0.25 cm), and DO (1.7±0.36 mg/l) lower than Brahmaputra river water. Temperature and PH were close to standard. The comparative study also revealed that the concentrations of heavy metals like Pb (0.032±0.003 mg/l), Cr (0.02±0.003 mg/l), Cd (0.02±0.005 mg/l), Ni (0.04±0.004 mg/l), Zn (0.08±0.005 mg/l) and Cu (0.01±0.002 mg/l) of Balu river water were higher than Brahmaputra River. In M. armatus, C. punctatus and M. vittatus, the concentration of heavy metals like Pb (0.85, 0.92 and 0.89 mg/kg), Cd (0.45, 0.48 and 0.51 mg/kg), Cr (0.72, 0.76 and 0.51 mg/kg), Cu (0.39, 0.38 and 0.35 mg/kg), Ni (0.95, 0.86 and 0.81 mg/kg) and Zn (1.17, 1.21 and 1.25 mg/kg) were noted in Balu river which were much higher than those of Brahmaputra river. Bioaccumulation of heavy metals in fish can increase with the increase of heavy metals in water if pollutants discharge simultaneously. The results suggested that the water in the Balu river was polluted and not suitable for human consumption and aquaculture. On the other hand water in the Brahmaputra river was usable for aquaculture and irrigation but gradually degrade its quality by growing industries and untreated waste from municipalities. Progressive Agriculture 27 (4): 444-452, 2016